Belonging and Longing: The Question of the Subject in Renaud Barbaras and Jean-Luc Marion - Szczepan Urbaniak (Text Matters)
The philosophy of Renaud Barbaras and Jean-Luc Marion departs from the transcendental role of the subject. No longer is the subject regarded as its own foundation, nor does it own or constitute its objects. Instead, it originates from some other principle and source. In order to comprehend why the subject loses its transcendental role, we first examine how the two phenomenologists perform the phenomenological reduction and to which more primordial instance than the subject itself it leads them. Consequently, we outline the tension inherent in the new understanding of the subject as one who receives itself from the givenness (Marion) or as life in the world and the desire of the world (Barbaras). The central theme of our study on the decentralized subject revolves around the concepts of belonging and longing. It can be argued that the essence and belonging of the subject lie in its desire and longing. Barbaras and Marion both consider the dimension of desire and love to be crucial for the subject. This essay seeks to highlight the commonalities and the reasons for the differences in their understanding of desire.